Регіон пострадянської Східної Європи в зовнішній політиці Великої Британії у контексті європейської інтеграції (1990-ті – 2010-ті рр.) - Грубінко, А. (Міжнародні зв’язки України: наукові пошуки і знахідки, 2019)
У статті представлено результати дослідження проблеми формування та реалізації східноєвропейської політики Великої Британії у 1990-х — 2010-х роках. Показано особливості політики Європейського Союзу щодо пострадянських країн Східної Європи (Росії, України, Білорусі, Молдови), роль Великої Британії у цьому процесі. Автор стверджує, що зовнішня політика Великої Британії щодо держав Східної Європи, зокрема, пострадянського простору, розвивалася в контексті загальної політики Заходу й відчувала сильний вплив російського чинника. Стратегічним завданням зовнішньої політики ЄС у нових геополітичних умовах стало забезпечення стабільності й безпеки на Сході Європи, просторах колишнього СРСР, насамперед у країнах найближчої периферії — Росії, Україні, Білорусі й Молдові. Незважаючи на вагому стратегічну роль регіону Східної Європи, його міжнародне значення ЄС і Велика Британія завжди недооцінювали. Остаточне послаблення впливу Великої Британії на східноєвропейську політику ЄС, що наступить унаслідок її виходу з об’єднання («Brexit»), матиме негативні наслідки для євроінтеграційних прагнень країн субрегіону. The article presents the results of the study problem of formation and implementation of Eastern European policy by Great Britain in the 1990s — 2010s. The features of the European Union’s policy towards the post-Soviet countries of Eastern Europe (Russia, Ukraine, Belarus, Moldova) and the role of Great Britain in this process are shown. The author argues that Britain’s foreign policy towards the countries of Eastern Europe, in particular the post- Soviet space, developed in the context of the general policy of the West and felt strongly influenced by the Russian factor. The strategic objective of the EU’s foreign policy in the new geopolitical environment has been to ensure stability and security in Eastern Europe, the former USSR, especially in the countries near the periphery. In 2002, the UK Government initiated the creation of a European Neighborhood Policy Mechanism. However, it was controversial. The democratic revolutions in Georgia and Ukraine in 2003–2004 did not lead to a radical revision of their relations with the EU. The intensification of tensions in the relations between the European Union, certain Western powers (in particular the United Kingdom) and Russia in the second half of the 2000s contributed to a certain intensification of their policy towards the post-Soviet states. However, the British governments have moved away from leading positions in the European Union integration policy and have taken a passive role in the Eastern Partnership program by giving the initiative to Germany. Despite the important strategic role of the Eastern European region, its importance to the EU and the United Kingdom has always been underestimated. It is concluded that the underestimation of security threats in Eastern Europe, along with the common problems of the Alliance’s development, have led to its inability to guarantee security at its eastern borders without the support of the US and NATO. The result is the United Kingdom, whose government, in the face of leaving the EU and losing influence in the Central Eastern Europe region, is interested in reorienting the United States to European security issues and stepping up NATO activities in Europe. With the UK leaving the EU, only real channel for its influence on the international situation in Eastern Europe will be US-backed NATO mechanisms. The completion of the Brexit process will weaken the position of Eastern European countries in their desire to become full members of the European Union.